Negationism and Invisibility: racism against indigenous peoples in brazilian education - Santos, Geisla Letícia Oliveira da Pureza (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
This study analyzes the invisibility of racism against indigenous peoples in the context of Brazilian education. From a critical and interdisciplinary approach, it examines how the school, by reinforcing stereotypes and omitting indigenous diversity and resistance, contributes significantly to the marginalization of these populations. Even with important legal milestones, such as Law 11.645/2008, which obliges the teaching of indigenous history and culture in schools, the national curriculum is still strongly marked by a Eurocentric perspective. This limitation prevents indigenous peoples from being recognized as historical subjects and holders of their own knowledge. The research highlights the need for educational policies committed to the inclusion of indigenous knowledge, representativeness in school content and the promotion of historical justice. It concludes that overcoming indigenous racism in Brazilian education requires concrete actions, such as valuing cultural diversity, critical and anti-racist training for education professionals and the construction of inclusive pedagogical practices.